Indian Constitution Vis-À-Vis The Idea of Secularism: The Role of State in The Ongoing Trends - Chaudhary, Divyanshu (Kathmandu School of Law Review, 2019)
We, the people of India, when the Constitution was drafted, adopted the magnificent path for the equal freedom of right to religion (under Article 25). However, 42nd Amendment, 1976 categorically made this path crystal clear by inserting the term “secular” within the preamble. It is, therefore, the intention of the Constitution makers which endorses the idea of secularism in India. India, that is to say, as a state has no religion but comes out as neutral towards the concept of religion. The Constitution, furthering the idea of values enshrined in the preamble, equally preserves and protects all religions. In this way, the state is certainly bound to abide by the Constitutional virtues of secularism; however, the ongoing trends in India depict otherwise. This paper, therefore, investigates these trends which seem to violate the secular idea of the Indian Constitutional philosophy. The researcher intends to establish as to how the state, in recent times, is involved in matters based on a specific religion and how it affects the very principles which were set by the Constitution makers. It is established that the ongoing trends in India have tremendously impacted the Constitutional ethos (including Constitutional morality) of secularism in India and the state has failed to keep them intact.